Contextualising Bickerton's Wainoni - Gatley, Julia (Architectural History Aotearoa, 2007)
Wainoni was the short-lived cooperative housing initiative of Canterbury College's "errant" Professor A. W. Bickerton, who from 1896 expanded his own house at Wainoni, near New Brighton, Christchurch, and invited like-minded others to join him and his family in living there. At the turn of the twentieth century, it accommodated about 30 residents. Bickerton called it a Federative Home. It has been referred to elsewhere as New Zealand's second cooperative house and was described within British Garden City Association discourse as a "very successful experiment" in cooperative housing, even though it failed within only a few years. This paper examines Wainoni within an Anglo/American context of cooperative housing and considers, in particular, issues of gender. It shows that the initiative was indeed experimental, not only for its communal living arrangements, but also because it demonstrates some reconsideration of entrenched work/home and male/female dichotomies. The challenge to established norms was not well received locally, in part because it was embedded within a broader critique of the institution of marriage.